Subgingival microbial profiles in chronic periodontitis patients from Chile, Colombia and Spain - David Herrera, Adolfo Contreras (Blackwell Synergy, 2008)
Aim: To investigate the subgingival microbiota of distinct periodontitis patient populations, in Chile, Colombia and Spain, using identical clinical and bacteriological methods. Material and Methods: In this multicentre study, 114 chronic periodontitis patients were selected. Patients were examined using an identical clinical protocol and pooled subgingival samples were obtained from each patient. Samples were processed in the three laboratories by means of culturing under identical clinical and microbiological protocols. Total anaerobic counts and frequency of detection and proportions of nine periodontal pathogens were calculated. Variables were analysed by means of ANOVA, w2, Kruskal–Wallis and Dunn’s multiple comparison tests. Results: The Colombian population demonstrated greater severity of periodontitis, with significantly deeper mean probing pocket depth, and had a significantly lower percentage of current smokers. When comparing samples from the three patient populations, the total counts were significantly higher in the Colombian patients. The numbers of putative pathogens differed among groups. Tannerella forsythia was found less frequently in Chilean samples, while Parvimonas micra and enteric rods differed significantly among the three population groups. Conclusion: Significant differences among Chile, Colombia and Spain existed regarding the frequency and proportions of specific periodontal pathogens in the subgingival microbiota of periodontitis patients.